Designing technologies for life cycle of associated products and waste in process of preparing production of a new automotive component - L. R. Safarova; S. V. Kasyanov; D. T. Safarov (Омский научный вестник)
The article presents an approach to minimizing the impact of automotive production on the natural environment, while minimizing the consumption of resources due to adequate planning of waste generation volumes in the workplace and the development of their life cycle processes at the stage of preparing the production of an automotive component. The algorithm of designing the manufacturing technology of automotive components with the development of processes for generating all types of associated products in the workplace is given. The blocks of calculation procedures are synchronized with the stages of preparation for the production of a new product in the automotive industry. A method of structuring the process has been developed, modeling of the content of intraoperative processes of creating a marketable product and the formation of time chains with subsequent planning for the removal of associated products, waste and emissions in the processes of functioning and maintenance of workplaces is carried out. Economic calculations are performed for decision-making by the engineering services of the enterprise.